Effect of Linker Structure on Salicylic Acid-Derived Poly(anhydride–esters) - Prudencio, Almudena (2005)
A series of salicylic acid-derived poly(anhydride–esters) were synthesized by melt polym erization methods, in which the structures of the molecule (“linker”) linking together the two salicylic acids were varied. To determine the relationship between the linker and the physical properties of the corresponding poly(anhydride–ester), several linkers were evaluated including linear aliphatic, aromatic, and aliphatic branched structures. For the linear aliphatic linkers, higher molecular weights were obtained with longer linear alkyl chains. The most sterically hindered linkers yielded lower molecular weight polymers. The thermal decomposition temperature increased with the alkyl chain length, but the glass transition temperature decreased, due to the enhanced flexibility of the polymer. The highest glass transition temperatures were obtained by using aromatic linkers as a result of increased π–π interactions. Water contact angles determined the relative hydrophobicity of the polymers, which correlated to hydrolytic degradation rates; i.e., the highest contact angle values yielded the slowest degrading polymers.